2012
DOI: 10.1088/0004-637x/755/2/129
|View full text |Cite
|
Sign up to set email alerts
|

Rebirth of X-Ray Emission From the Born-Again Planetary Nebula A30

Abstract: The planetary nebula (PN) A 30 is believed to have undergone a very late thermal pulse resulting in the ejection of knots of hydrogen-poor material. Using multi-epoch HST images we have detected the angular expansion of these knots and derived an age of 850 +280 −150 yr. To investigate the spectral and spatial properties of the soft X-ray emission detected by ROSAT, we have obtained Chandra and XMM-Newton deep observations of A 30. The X-ray emission from A 30 can be separated into two components: a point-sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 57 publications
4
49
1
Order By: Relevance
“…If observed at this particular moment in time, the outer, eye-like shell may be visible as a halo around the PN. Such halos have been observed for several PNe, such as Abell 30 (Guerrero et al 2012) and NGC 6751 (Clark et al 2010), but are usually spherical in shape and can also be attributed to mass ejecta from a thermal pulse rather than the wind-ISM interaction. When the PN hits the termination shock of the the AGB wind bubble (right panel of Fig.…”
Section: Resultsmentioning
confidence: 93%
“…If observed at this particular moment in time, the outer, eye-like shell may be visible as a halo around the PN. Such halos have been observed for several PNe, such as Abell 30 (Guerrero et al 2012) and NGC 6751 (Clark et al 2010), but are usually spherical in shape and can also be attributed to mass ejecta from a thermal pulse rather than the wind-ISM interaction. When the PN hits the termination shock of the the AGB wind bubble (right panel of Fig.…”
Section: Resultsmentioning
confidence: 93%
“…This may also be the case for A 43 and Lo 4 although the large number of narrow absorptions over-imposed on the profile makes it hard to determine; the remaining objects show unsaturated P Cygni profiles. All the CSPNe with P Cygni profile in the Ne vii line have T eff > 100 000 K ( NGC 2371-2, NGC 7094, and RX J2117.4+3412 is detected in soft X-rays (Motch et al 1993;Hoare et al 1995;Kastner et al 2012), whereas A 30's central star's soft X-ray emission may have a different origin (Guerrero et al 2012 Despite this difficulty, the P Cygni profiles of the two components can be used to lend weight to the determination of the line profile. Owing very likely to the sulfur abundance in the stellar wind being lower than that of oxygen, the S vi lines are saturated just in three CSPNe (IC 2501, NGC 5882, and NGC 6572) out of the 15 displaying it.…”
Section: Atlas Of Fuse P-cygni Profiles Of Cspnementioning
confidence: 99%
“…Among these CSPNe, three objects with variable FUSE P Cygni profiles are hard X-ray emitters (NGC 2392, NGC 6543, and NGC 6826), while three others (BD+30 • 3639, IC 418, and NGC 40) are not (Kastner et al 2000;Guerrero et al 2001;Montez et al 2005;Kastner et al 2012, Guerrero et al, in prep.). Among the CSPNe without P Cygni profiles or non-variable P Cygni profiles, seven are found to lack hard X-ray emission (Hen 2-99, GJJC 1, NGC 1360, NGC 3132, NGC 3587, NGC 6720, and NGC 7662), whereas another seven (A 30, K 1-16, NGC 246, NGC 2371-2, NGC 7009, NGC 7094, and NGC 7293) are hard X-ray emitters (Guerrero et al , 2012Kastner et al 2012;Montez & Kastner 2013), although their FUSE spectra are not always of sufficient quality to search for variability.…”
Section: Correlation Between Hard X-rays and Wind Variabilitymentioning
confidence: 99%
“…A Chandra or XMM gratings spectroscopy observation of K 1-16 could confirm the presence of the hot, carbon-rich plasma inferred from our CCD spectra, and might further constrain its density, but such a program will be exceedingly difficult due to the low count rate from K 1-16 and contamination by the ICM X-ray emission. Indeed, Guerrero et al (2012) reported detection of a Cvi emission line at ∼0.37 keV in their XMM Reflection Grating Spectrometer (RGS) spectrum of the PG1159-type CSPN of A30. The lower-resolution CCD X-ray spectrum of A30 appears similar to that of K 1-16; however, since Guerrero et al (2012) do not employ an NLTE component in their analysis of the A30 CSPN gratings X-ray spectrum, a direct comparison cannot be made.…”
Section: Origin Of the Mk Plasmamentioning
confidence: 99%
“…Indeed, Guerrero et al (2012) reported detection of a Cvi emission line at ∼0.37 keV in their XMM Reflection Grating Spectrometer (RGS) spectrum of the PG1159-type CSPN of A30. The lower-resolution CCD X-ray spectrum of A30 appears similar to that of K 1-16; however, since Guerrero et al (2012) do not employ an NLTE component in their analysis of the A30 CSPN gratings X-ray spectrum, a direct comparison cannot be made. The similarities between K 1-16 and A30 extend to the X-ray spectrum of the PG1159 CSPN of NGC 246, for which Hoogerwerf et al (2007) has suggested the presence of a complex of carbon lines.…”
Section: Origin Of the Mk Plasmamentioning
confidence: 99%